Understanding the Varieties of Research Experience: Stories of Undergraduate Students - Moch. Sabrowi; Mohammad Adnan Latief; Yazid Basthomi (Jurnal Pendidikan Humaniora, 2020)
Abstract: Engaging in research can benefit students in several ways. However, higher learning institutions have been challenged to engage students in research experiences. The present study is conducted to discover what undergraduate students experience in the research process, and how they accomplish their tasks during the process. Narrative research is used for this study to understand present real-life experiences. The study revealed that students experience different conditions and apply various techniques in the research process. Besides, when they encountered the same or similar challenges, they were prone to accomplish their tasks with the same attempt.Key words: research experience, students’ task accomplishment, narrative inquiryAbstrak: Terlibat dalam penelitian dapat bermanfaat bagi mahasiswa dalam berbagai cara. Namun, lembaga pendidikan tinggi tertantang untuk melibatkan siswa dalam pengalaman penelitian. Penelitian ini dilakukan untuk menemukan apa yang dialami mahasiswa sarjana dalam proses penelitian, dan bagaimana mereka menyelesaikan tugas-tugas mereka selama proses tersebut. Penelitian naratif digunakan dalam penelitian ini untuk memahami pengalaman kehidupan nyata saat ini. Studi ini mengungkapkan bahwa mahasiswa mengalami kondisi yang berbeda dan menerapkan berbagai teknik dalam proses penelitian. Selain itu, ketika mereka menghadapi tantangan yang sama atau serupa, mereka cenderung menyelesaikan tugas-tugas mereka dengan usaha yang sama.Kata kunci: pengalaman meneliti, penyelesaian tugas mahasiswa, investigasi naratif